Pathways And Pilgrimages: The In-Between Spaces in the Patria Cycle - Galloway, Kate (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2007)
AbstractIn R. Murray Schafer’s Patria cycle (1966–), movement, both choreographed and improvisational—to the performance, between spaces within the performance, and within the fabrication of the performance—allows the audience to actively participate. These in-between spaces of movement are as much performance space as is the final site of the production, extending the performance beyond the confines of the theatre. Drawing on examples from The Princess of the Stars, The Enchanted Forest, and The Greatest Show, this article examines two states of in-betweenness: first, the pilgrimage to the performance, and second, the pathways that link performance experiences.